2013
DOI: 10.1097/01.adm.0000435321.39251.d7
|View full text |Cite
|
Sign up to set email alerts
|

Safe Methadone Induction and Stabilization

Abstract: Careful management of methadone induction and stabilization, coupled with patient education and increased clinical vigilance, can save lives in this vulnerable patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…Interestingly, that study used methadone as a control for μ-opioid receptor activity and indicated that, similar to the low doses of buprenorphine, exposure of oligodendrocytes to methadone resulted in increased MBP expression. That initial clue suggested that myelination could also be directly affected by methadone, a problem of significant importance as this synthetic opioid is currently used in opioid detoxification treatments for pregnant addicts and their newborns [32]. We now report that, at least in the rat brain, early myelination is indeed altered by perinatal exposure to therapeutic levels of methadone.…”
Section: Introductionmentioning
confidence: 80%
“…Interestingly, that study used methadone as a control for μ-opioid receptor activity and indicated that, similar to the low doses of buprenorphine, exposure of oligodendrocytes to methadone resulted in increased MBP expression. That initial clue suggested that myelination could also be directly affected by methadone, a problem of significant importance as this synthetic opioid is currently used in opioid detoxification treatments for pregnant addicts and their newborns [32]. We now report that, at least in the rat brain, early myelination is indeed altered by perinatal exposure to therapeutic levels of methadone.…”
Section: Introductionmentioning
confidence: 80%
“…• Health Canada exemption is required to prescribe methadone in all provinces and territories • Higher risk of overdose 19,24,25,36 • More often prescribed as witnessed doses; prescription of take-home doses typically use slow graduated schedule (e.g., increase of 1 takehome dose per week about every 4 weeks), which can be inconvenient or not feasible for some patients • More severe adverse effect profile (e.g., somnolence, erectile dysfunction, cognitive blunting) 22,23 • Longer time to achieve therapeutic dose (several weeks) 36 • Can be more challenging to transition from methadone to buprenorphine-naloxone if treatment is unsuccessful 22,23 • Higher risk of public safety harms if diverted 26,27 • Higher potential for adverse drug-drug interactions (e.g., antibiotics, antidepressants, antiretrovirals) 31 • Associated with QTc prolongation and increased risk of cardiac arrhythmia in patients prescribed higher doses, with pre-existing risk factors or taking other medication(s) that prolong QTc interval 22,23 • Can be more expensive if prescribed as daily witnessed doses, mainly owing to fees associated with dispensing and witnessed ingestion 34,35 • Potentially lower treatment retention, particularly in higherintensity opioid use disorder with low-dose buprenorphinenaloxone 18 • May cause precipitated withdrawal if appropriate dose-induction protocols are not followed 30 • Suppression of withdrawal symptoms may be inadequate for individuals with high opioid tolerance 22,23 • Reversing effects of overdose can be challenging because of the pharmacology of buprenorphine (i.e., high affinity for opioid receptors and long half-life) 31 • Patients require education on how to take sublingual doses correctly (i.e., hold under tongue until dissolved -up to 10 minutes; do not drink or smoke, and minimize swallowing) • Nonadherence to treatment may require frequent reinductions Note: QTc = corrected QT.…”
Section: Disadvantagesmentioning
confidence: 99%
“…initiating and/or receiving methadone, which, owing to its long-half, is recognized for risk of toxic accumulation during the start of therapy [30, 31],…”
Section: Naloxone Overdose Prevention: Targeting At-risk Chronic Painmentioning
confidence: 99%